Comparing MicroRNA Profilings of Purified HER-2-Negative and HER-2-Positive Cells Validates miR-362-5p/Sema3A as Characteristic Molecular Change in Triple-Negative Breast Cancers. (18th December 2019) - Zhang, Xiaoqing; He, Qi; Sun, Leiqin; Zhang, Yanfei; Qin, Shengying; Fan, Junwei; Wang, Jianfeng
Abstract : Background . HER-2 is a key molecule serving as the therapeutic target, prognostic biomarker, and classification marker in breast cancer. Accurate microRNA profilings had not been conducted in purified tumor cells of HER-2-negative and HER-2-positive tissue specimens obtained from breast cancer patients. Methods . (i) Differential expression microRNA discovery using laser capture microdissection- (LCM-) assisted specimen preparation and microRNA array chips on HER-2 overexpressing and triple-negative breast carcinoma (TNBC) subtype tissues, (ii) differential expression microRNA validation by quantitative real-time PCR, and (iii) independent validation on tissue microarray. Results . Five microRNAs (miR-20a-5p, miR-221-3p, miR-362-5p, miR-502-3p, and miR-222-3p) were screened and validated as upregulated microRNAs in TNBC cells comparing to HER-2 overexpressing cells using a microRNA array (5 cases in each group) and quantitative real-time PCR (20 cases in each group). The expression difference of miR-362-5p had the most significant statistical significance (p = 0.0016 ) among the five microRNAs. The expression of miR-362-5p and its target gene Sema3A was further analyzed using in situ hybridization (ISH) and immunohistochemistry on standard tissue sections (n = 150 ). 70.8% of HER-2-negative cells showed moderate expression of miR-362-5p whereas 20.4% HER-2-negative cells correlated with strong expression of miR-362-5p (p < 0.0001 ). The proportion of patients with moderate/strong miR-362-5p expression in luminal, HER-2 overexpressing, and TNBC subtypes were 53.2%, 22.2%, and 74.3%, respectively (p = 0.0002 ). High miR-362-5p expressers had shorter overall survival in the univariate analysis (p = 0.046 ). There was a significant negative correlation between miR-362-5p and Sema3A expression (p < 0.0001 ). The patients with negative/weak Sema3A protein expression had poorer prognosis than those with moderate (HR: 3.723, p = 0.021 ) or strong (HR: 3.966, p = 0.013 ) Sema3A protein expression in the multivariate analysis. Conclusions . miR-362-5p/Sema3A might provide a promising therapeutic pathway and represents a candidate therapeutic target of the TNBC subtype.